Amalan Keselamatan dan Kesihatan Pekerjaan Dalam Aspek Pengendalian Jentera Berat - Zulhisham, Fatin Nabilah; Shafii, Haryati; Md Yassin, Azlina; Masram, Haidaliza; Omar, Roshartini (Research in Management of Technology and Business, 2023)
The construction industry is an industry that has a high risk of occupational accidents because the industry is constantly changing according to the progress of the project phase. The problem statement for this study is the issue of occupational health and safety practices among workers involving the use of heavy machinery which causes an increased risk of accidents for workers on construction sites. The three objectives to be achieved through this study are to identify accidents related to the operation of heavy machinery in the construction industry, examine the factors that affect safety and health practices among workers during the operation of heavy machinery and suggest measures that need to be taken by the management to reduce worker accidents involving heavy machinery. This study will be conducted using qualitative methods. Respondents for this study are operators who use heavy machinery, construction site health and safety officers, and construction site supervisors who are managing heavy machinery handling operations on construction sites. The scope of this study is focused on several construction projects that use heavy machinery carried out around the Federal Territory of Kuala Lumpur. Then, the data will be analyzed using thematic analysis. Through the results of the study from the analysis of interview data, there are four types of accidents that occur involving various types of heavy machinery. In addition, project or construction site condition factors, environmental factors, human factors, and safety management factors are factors that influence safety and health practices among workers during heavy machinery handling operations. As for the recommendations, there are several improvement measures that need to be carried out by the management to reduce worker accidents involving heavy machinery. It is hoped that this study will provide space for future studies to study more in-depth about occupational safety and health practices in the aspect of handling heavy machinery at construction sites. Keywords: Heavy Machinery, Safety, Health, Practices